Search for pair production of second-generation scalar leptoquarks in pp collisions at √s = 7 TeV. - Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; Ghete, V; Hammer, J; et al. (2011)
A search for pair production of second-generation scalar leptoquarks in the final state with two muons and two jets is performed using proton-proton collision data at √s = 7 TeV collected by the CMS detector at the LHC. The data sample used corresponds to an integrated luminosity of 34 pb⁻¹. The number of observed events is in good agreement with the predictions from the standard model processes. An upper limit is set on the second-generation leptoquark cross section times β² as a function of the leptoquark mass, and leptoquarks with masses below 394 GeV are excluded at a 95% confidence level for β = 1, where β is the leptoquark branching fraction into a muon and a quark. These limits are the most stringent to date.